The Influence of Screen Time on Flexibility and Muscular Endurance in adolescents. - Mansi George1, Sandeep Dhull2 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Introduction: With the increasing reliance on digital devices, adolescents are spending prolonged hours on screens, raising concerns about its impact on physical fitness. Excessive screen time contributes to sedentary behavior, which may affect flexibility and muscular endurance, two essential components of overall health and functional movement. This study aims to examine the differences in flexibility and muscular endurance across varying levels of screen time among adolescents. Methodology: A cross-sectional study was conducted among 500 adolescents, categorized into three screen time groups: 0-60 minutes, 60-180 minutes, and 180 minutes or more per day. Flexibility and muscular endurance were assessed using standardized tests. Normality was evaluated using Kolmogorov-Smirnov and Shapiro-Wilk tests, and since the data were non-normally distributed (P < 0.05), the Kruskal-Wallis test was applied to compare differences across screen time groups. Results: The Kruskal-Wallis test revealed significant differences in both flexibility (H = 9.1, P = 0.011) and muscular endurance (H = 33.208, P = 0.001) across screen time levels. Adolescents with higher screen time (≥180 min/day) had the highest mean ranks for both fitness measures, suggesting variability in physical activity engagement within this group. However, prolonged screen exposure remains a risk factor for reduced physical activity levels, muscle weakness, and postural imbalances. Conclusion: The study highlights the importance of balancing screen time with physical activity to maintain flexibility and muscular endurance in adolescents. While some high screen-time users may engage in active screen-based activities, excessive sedentary behavior can negatively affect musculoskeletal health. Future research should focus on differentiating between passive and active screen use and developing guidelines to mitigate the adverse effects of prolonged screen exposure.